Colocalization of insulin-like growth factor-1 receptor and T type Cav3.2 channel in dorsal root ganglia in chronic inflammatory pain mouse model. Issue 10 (6th July 2016) - Lin, Si-Fang; Yu, Xiao-Lu; Wang, Bing; Zhang, Ya-Jun; Sun, Yan-Gang; Liu, Xing-Jun
Abstract : Insulin-like growth factor-1 (IGF-1) is a neurotrophic factor and plays important roles in the nervous system. Increasing evidence supports that IGF-1 contributes to pain hypersensitivity through its insulin-like growth factor-1 receptor (IGF-1R) by activating IGF-1R/Akt or MAPK signaling pathways, whereas T-type Cav 3.2 channel can facilitate and amplify pain signals originating from the sensory periphery. A recent study showed that activated IGF-1R can increase T-type Cav 3.2 channel currents and further activate the G protein-dependent PKCα pathway to contribute to inflammatory pain sensitivity. However, the colocalization of IGF-1R and Cav 3.2 in mouse dorsal root ganglion (DRG) under chronic inflammatory pain conditions remains elusive. In this study, we investigated changes in the expression of IGF-1R and the Cav 3.2 channel, and their colocalization in mouse DRGs in chronic inflammatory pain condition (induced by complete Freund's adjuvant intraplanter injection) using real-time RT-PCR and immunohistochemistry approaches to confirm that Cav 3.2 channel can mediate pain facilitation following IGF-1/IGF-1R signaling. We found that IGF-1R was expressed extensively in DRG neurons including small-, medium-, and large-sized neurons, whereas Cav 3.2 channel was expressed exclusively in small-sized DRG neurons of naive mice. Expression of Cav 3.2, but not IGF-1R, and colocalization of Cav 3.2 and IGF-1R were increased in lumbar (L)4–L6 primary sensory neurons in DRGs of mice in chronic inflammatory pain. Moreover, the increased colocalization of IGF-1R and Cav 3.2 is exclusively localized in small- and medium-sized primary sensory neurons. Our findings provided morphological evidence that T-type Cav 3.2 channel, at least partially, mediates the pain facilitation of IGF-1/IGF-1R signaling in chronic inflammatory pain condition.